Hygiene knowledge and practices in the Lagos wild meat value chain: Cultural influences, regulatory gaps, and infrastructure needs - Akpan, Samuel N.; Cook, Elizabeth A.J.; Langevelde, F. van; Hooft, P. van; Zimmerman, D.M.; Buij, R.; Hassell, James M.; Masudi, Sherril P.; Happi, C.T.; Happi, A.N.; Thomas, Lian F. (Public Library of Science, 2026)
Wild meat, commonly known as bushmeat, is a cultural, economic, and nutritional staple food in many regions of the world, including sub-Saharan Africa. Wild meat value chains face major hygiene and sanitary regulation challenges, but only a few studies have investigated these challenges, focusing instead on market dynamics and biodiversity issues. This study examines the hygiene practices, attitudes, perceptions, and knowledge of public health risks among actors in the Lagos (Nigeria) wild meat value chain, and its consequences for food safety. We employed a qualitative study design, using in-depth interviews of key informants (n = 34) purposively selected from the wild meat value chain’s hunter, wholesaler, processor, and retailer nodes. An inductive thematic approach was used for data analysis. Results revealed three overarching themes: culture, infrastructure, and regulation. Social norms, poor infrastructure, and lack of regulation were the main drivers of the hygiene practices in the value chain. Actors showed poor knowledge of the health risks associated with wild meat, prioritizing taste over its safety. Women were more at risk of contracting zoonotic infections due to gender biases, which exposed them to riskier nodes of the value chain. The wild meat value chain in the megacity of Lagos constitutes a high-risk platform for zoonotic and food-borne pathogen transmission, due to poor knowledge, infrastructure deficits, and economic resource pressure, which leads to unhygienic practices of its actors. We recommend intervention approaches that integrate people’s cultures, provision of infrastructure, enforcement of sanitary standards, actors’ education, and further empirical research to stimulate the establishment of hygiene guidelines for the regulation of urban wild meat value chains globally.